Autism breakthrough : the groundbreaking method that has helped families all over the world - Kaufman Raun K. (London Vermilion, 2014)
When Raun Kaufman's parents were told that their son was autistic and would probably spend his life in an institution, they decided to look for their own solution. They joined Raun in his unique, isolated world and connected with him there. They then gradually lead Raun out of his disorder and his life changed dramatically.